SENTIMEN ANALISIS ULASAN PENGGUNA GOJEK MENGGUNAKAN ALGORITMA MACHINE LEARNING SUPPORT VECTOR MACHINE - Sandiva, Tesa Vausia; Kristiyanto, Arip; Sandi, Leo (STMIK BINA PATRIA, 2025)
The development of digital technology has brought significant changes to various sectors of life, including the transportation sector. One popular mode of transportation among the public is online motorcycle taxis, such as Gojek. Gojek continues to innovate to meet customer needs more effectively and expand its service coverage. This study aims to identify the number of positive, neutral, and negative sentiments in a user review dataset, as well as evaluate the performance of the SVM algorithm used. The analysis was conducted on 10,000 customer reviews from the Play Store application, resulting in 2,057 positive sentiments, 1,135 neutral sentiments, and 6,295 negative sentiments. The classification model employed, namely SVM, achieved an accuracy of 89% and an F1-score of 90%.